Insulin-like growth factor 2 (IGF-2) rescues social deficits in NLG3–/y mouse model of ASDs - Pizzarelli, Rocco; Pimpinella, Domenico; Jacobs, Christian; Tartacca, Alice; Kullolli, Uarda; Monyer, Hannah; Alberini, Cristina M.; Griguoli, Marilena (Frontiers in Cellular Neuroscience, 2024)
Autism spectrum disorders (ASDs) comprise developmental disabilities characterized by impairments of social interaction and repetitive behavior, often associated with cognitive deficits.There is no current treatment that can ameliorate most of the ASDs symptomatology; thus, identifying novel therapies is urgently needed. Here, we used the Neuroligin 3 knockout mouse (NLG3 -/y ), a model that recapitulates the social deficits reported in ASDs patients, to test the effects of systemic administration of IGF-2, a polypeptide that crosses the blood-brain barrier and acts as a cognitive enhancer. We show that systemic IGF-2 treatment reverses the typical defects in social interaction and social novelty discrimination reflective of ASDs-like phenotypes. This effect was not accompanied by any change in spontaneous glutamatergic synaptic transmission in CA2 hippocampal region, a mechanism found to be crucial for social novelty discrimination. However, in both NLG3 +/y and NLG3 -/y mice IGF-2 increased cell excitability. Although further investigation is needed to clarify the cellular and molecular mechanisms underpinning IGF-2 effect on social behavior, our findings highlight IGF-2 as a potential pharmacological tool for the treatment of social dysfunctions associated with ASDs.